Odpowiedzi

Najlepsza Odpowiedź!
2010-02-14T19:27:46+01:00
A) 6y-1=y+9
6y -y = 9 +1
5y = 10
y = 10 : 5
y = 2

b) 6-5x=2x-7
-5x -2x = -7 -6
-7x = -13
x = (-13):(-7)
x = 13/7
x = 1 i 7/7

c) -5t+1=8-6t
-5t + 6t = 8 -1
t = 7
1 5 1
2010-02-14T19:28:15+01:00
A)
6y-1=y+9
6y -y = 9 +1
5y = 10 /:5
y = 2

b)
6-5x=2x-7
-5x -2x = -7 -6
-7x = -13 /: (-7)
x = 13/7
x = 1 i 7/7

c)
-5t+1=8-6t
-5t + 6t = 8 -1
t = 7

;]]
1 1 1
2010-02-14T19:30:04+01:00
A) 6y-y=9+1
5y=10
y=2
b)6-5x=2x-7
-5x-2x=-7-6
-7x=-13
x=13/7
c) -5t+1=8-6t
-5t+6t=8-1
t=7
1 1 1